MANFAAT BIOMASA TUMBUHAN LOKAL UNTUK MENINGKATKAN KETERSEDIAAN NITROGEN TANAH DI LAHAN KERING MALANG SELATAN - Dewi, E. K.; Handayanto, E. (BUANA SAINS, 2006)
A research that was aimed to study the possible use of Mucuna pruriens, Psophocarpus tetragonolubus, Phaseolus lunatus, Dolichos lablab biomass as sources of local organic matters to improve soil fertility, and growth of maize on a Typic Tropaquent of South Malang. Six treatments, i.e. Mucuna pruriens, Psophocarpus tetragonolubus, Phaseolus lunatus, Dolichos lablab, Urea, and Control (no added legume biomass and fertilizers), were arranged in a Randomized Block Design with three replicates. Results of the study showed that the highest increase of soil N was due to addition of Phaeseolus, followed by Dolichos, Mucuna, and Psophocarpus. Application of Dolichos, Phaseolus, Psophocarpus and Mucuna could substitute 66%, 36%, 30% and 28% of N supplied by urea, respectively. The percentage of N urea recovered by maize was only 23,60%, while Dolichos and Phaseolus treatments resulted in 29,60% and 24,80% N recovery